Innovative Web Applications for Analyzing Traffic Operations - Petrovska, Natasha; Stevanovic, Aleksandar; Furht, Borko; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
In response to the need to improve road traffic operation, researchers implement advanced technologies and integration of systems and data, and develop state-of-the-art applications to assist traffic engineers. This SpringerBrief introduces three novel Web applications which can be an exceptional resource and a good visualization tool for traffic operators, managers, and analysts to monitor the congestion, and analyze incidents and signal performance measures. The applications offer more detailed analysis providing users with insights from different levels and perspectives. The benefit of providing these automated and interactive visualization tools is more efficient estimation of the local transport networks' performance, thus facilitating the decision making process in case of emergency events. .
Introduction -- Background and Related Work -- Visualization Tools for Traffic Congestion Estimation -- Web Application for Incident Analysis -- Web Application for Measuring Travel-Based Time Signal Performance -- Conclusion. .
Keywords: Computer science; Computer organization; Data mining; Computer Science; Computer Systems Organization and Communication Networks; Data Mining and Knowledge Discovery